The Analysis of the Influence of Religion on Economic Growth in the Context of Max Weber’s Views (Economic and Political Thought, 2018)
The basis of Weber thesis is presented in the work The ProtestantEthic and the Spirit of Capitalism. Analysing the development of capitalismWeber connected it, among others, with an increase of rationality causedby a particular religion. He stated that an increase in ascetic Protestantism(including Calvinism), and in particular a set of values and beliefs about work,savings, investment, and multiplying wealth were essential to the creation ofmodern capitalism.The author conducted a verification of Weber’s thesis and used his owneconometric model for the economy of Germany. The Protestant religion,in addition to the level of emigration, the proportion of people working inagriculture, was important for the creation of social welfare (GDP). This isa negative relationship as an increase in the number of Protestants led toa decrease in GDP growth. At the same time, it should be noted that thepercentage of the number of Protestants in the German Reich decreasedduring the analysed period. The relatively low coefficient of determinationalso indicates that the model explains 33.13% of the cases.
Keywords: economic growth and Protestantism, the German Reich, Max Weber, cliometrics